2019
DOI: 10.1007/s11255-019-02192-4
|View full text |Cite
|
Sign up to set email alerts
|

Postural stability during standing and its association with physical and cognitive functions in non-dialysis chronic kidney disease patients

Abstract: Purpose Chronic kidney disease (CKD) is characterised by poor physical function. A possible factor may be aberrant changes to balance and postural stability (i.e. ability to maintain centre of pressure (COP)). Previous research has exclusively focused on patients undergoing renal replacement therapy (RRT). The current study investigated postural stability in a group of CKD patients not requiring RRT. Methods 30 CKD patients (aged 57.0 ± 17.8 years, 47% female, mean eGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…After controlling for covariates, the cognitively impaired group was found to have significantly slower gait speed, highlighting the potential for co-occurrence of physical and cognitive symptoms, even in predialysis patients (Otobe et al, 2019). Similarly, in a cross-sectional study, Wilkinson and colleagues (2019) found that poorer postural stability was strongly correlated with lower MOCA-Basic scores in a population of nondialysis CKD patients ( N = 30, M age = 57). Overall, screening for cognitive impairment in this population is important given the risk for association with adverse health variables.…”
Section: Results Of Scoping Reviewmentioning
confidence: 77%
“…After controlling for covariates, the cognitively impaired group was found to have significantly slower gait speed, highlighting the potential for co-occurrence of physical and cognitive symptoms, even in predialysis patients (Otobe et al, 2019). Similarly, in a cross-sectional study, Wilkinson and colleagues (2019) found that poorer postural stability was strongly correlated with lower MOCA-Basic scores in a population of nondialysis CKD patients ( N = 30, M age = 57). Overall, screening for cognitive impairment in this population is important given the risk for association with adverse health variables.…”
Section: Results Of Scoping Reviewmentioning
confidence: 77%
“…Better functional capacity is indicated by a quicker time 21 . Balance and postural stability (postural sway and velocity) was assessed using a FysioMeter device that measures force distribution and resultant centre of pressure (COP) displacement 22 . Patients stood bipedal on the board with their feet shoulder‐width apart and their eyes open.…”
Section: Methodsmentioning
confidence: 99%
“…Postural stability and balance will be assessed using a previously reported method 72 with a FysioMeter device (modified Nintendo Wii balance board (Nintendo, Kyoto, Japan)) connected via Bluetooth to software on a portable computer (FysioMeter, Brønderslev, Denmark). Total centre of pressure ellipse area (mm 2 ) will be obtained.…”
Section: Methods and Analysismentioning
confidence: 99%